Impact of CardioMEMS device placement on lifestyle modifications: a "pseudo-placebo" effect beyond the expected?. Issue 8 (August 2018) - Assaad, Mahmoud; Singh, Robby; Sarsam, Sinan; Bowen, Abbie; Zughaib, Marcel
Introduction: Congestive heart failure is a leading cause of cardiovascular mortality and morbidity in the United States and places a significant economic burden on the health care system. The CHAMPION trial showed significant reductions in heart failure hospitalizations and length of stay as well as improvements in quality of life among patients who underwent implantation of the CardioMEMS device (CardioMEMS Inc., Atlanta, GA, USA). While the benefits of the device have been well demonstrated, we explored the "pseudo-placebo" effect of device placement on patients' lifestyle modifications. Methods: Thirty patients with the CardioMEMS device were contacted for a follow-up survey that included questions about lifestyle modifications, symptomatic and dietary improvement, increased physical activity, and changes in their cardiac medication regimen. Results: Dyspnea improved in 57% of patients, 70% of patients improved their diet, and 43% increased their physical activity. Only 7% of patients found it difficult to transmit the data. Discussion: The CHAMPION trial showed numerous benefits for patients who underwent CardioMEMS device placement. In our study, we found that device placement also resulted in a "pseudo-placebo" effect with most patients making positive lifestyle modifications.